Tourism, Energy Consumption and Climate Change in OECD Countries - Tiwari, Aviral Kumar; Ozturk, Ilhan; Aruna, M. (International Journal of Energy Economics and Policy, 2013)
<!--[if gte mso 9]> 800x600 <![endif]--> The study analyzed dynamics of the relationship between tourism, energy consumption, and climate change for 25 OECD countries during 1995-2005. For the analysis, Panel VAR (PVAR) model was used. Results of panel unit root-tests show that tourism is nonstationary in the level form but stationary in first difference form and energy consumption and climate change are stationary variables in the level form. Analysis of bivariate model shows that results are sensitive with change in the measurement of the tourism variable, change in order of variable and inclusion of the third variable. However, results of our trivariate model are found to be insensitive with either the change in the measurement of our tourism variable or change in the ordering of the variables. Our results of IRFs shows that response of tourism in one SD shock in climate change and energy consumption and response of climate change emissions to tourism is marginally positive. Further, we find that response of climate change in one SD shock in energy consumption and response of energy consumption in one SD shock in tourism and climate change is zero. Keywords: Tourism; energy consumption; climate change; OECD countries; panel VAR JEL Classifications: L83; O13; Q4; Q5 <!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]-->